2015
DOI: 10.1515/johh-2015-0028
|View full text |Cite
|
Sign up to set email alerts
|

Using thermal tracers to estimate flow velocities of shallow flows: laboratory and field experiments

Abstract: Accurate measurement of shallow flows is important for hydraulics, hydrology and water resources management. The objective of this paper is to discuss a technique for shallow flow and overland flow velocity estimation that uses infrared thermography. Laboratory flumes and different bare, vegetated and paved field surfaces were used to test the technique. Results show that shallow flow surface velocities estimated using thermal tracers and infrared technology are similar to estimates obtained using the Acoustic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…infrared video camera). Thermal tracers were tested as instruments to measure flow velocities (Schuetz et al, 2012;de Lima and Abrantes, 2014b;de Lima et al, 2015;Bonner et al, 2017), as well as for assessing microrelief (Abrantes and de Lima, 2014; de Lima and Abrantes 2014a), permeability (de Lima et al, 2014b), macroporosity (de Lima et al, 2014a,c) and repellency of the soil surface (Abrantes et al, 2016(Abrantes et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…infrared video camera). Thermal tracers were tested as instruments to measure flow velocities (Schuetz et al, 2012;de Lima and Abrantes, 2014b;de Lima et al, 2015;Bonner et al, 2017), as well as for assessing microrelief (Abrantes and de Lima, 2014; de Lima and Abrantes 2014a), permeability (de Lima et al, 2014b), macroporosity (de Lima et al, 2014a,c) and repellency of the soil surface (Abrantes et al, 2016(Abrantes et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Tracking reliability is much lower in these textureless regions. Note that reliability of thermal image‐based flow velocity measurement is influenced by the amount and location of the inserted hot water (Lima et al, ). For example, velocity results at M7 could not be retrieved during image sequence 2, because the location of the hot water insertion was too far away from the measurement area, which lead to missing textures.…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of our results with previously published work is conducted, focusing on the utilization of thermal data. Lima et al (2015) observed that standard deviation values vary between 0.004 and 0.018 m/s for velocities between 0.08 and 0.2 m/s using the method of leading edge estimation in laboratory experiments with an acoustic Doppler velocimeter as reference device. Thus, the coefficient of variation, which is defined by the ratio of standard deviation to mean, fluctuates from 5% to 9%.…”
Section: 1029/2018wr024507mentioning
confidence: 99%
See 1 more Smart Citation
“…There are many low-cost options of high-resolution optical cameras that can observe up to hundreds of square kilometres (Aschenwald, Leichter, Tasser, & Tappeiner, 2001;Salvatori et al, 2011). Thermal cameras of similar resolution are usually significantly more expensive, and they are commonly used for smaller areas of a few square metres (de Lima, Abrantes, de Lima, & de Lima, 2015;de Lima, Abrantes, Silva, de Lima, & Montenegro, 2014;Röper, Greskowiak, & Massmann, 2014) when used in a terrestrial mode.…”
mentioning
confidence: 99%